2020
DOI: 10.1080/02701367.2020.1799916
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and Health-Related Outcomes of Beginner Running Programs: A 10-Week Observational Study

Abstract: Purpose: This study aimed to explore the determinants of adherence and assess changes in fitness and health outcomes in participants of group-based beginner running programs. Methods: Participants completed adherence diaries (n = 34) during the 10-week program and underwent fitness and health testing (n = 20) at the program start and end. Diaries included weekly visual analogue scales of enjoyment, motivation, confidence, fatigue, satisfaction and support along with a record of training sessions. Space was pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The overall adherence to the training programs is highly associated with the injury rate, enjoyment, motivation, and satisfaction with progress [ 61 ]. In this regard, the absence of injuries or complaints and the improvements in physical performance observed during this pilot study, in conjunction with previous adherence in experimental studies [ 32 , 35 , 62 ], bring increased expectations for a good adherence to the training program in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…The overall adherence to the training programs is highly associated with the injury rate, enjoyment, motivation, and satisfaction with progress [ 61 ]. In this regard, the absence of injuries or complaints and the improvements in physical performance observed during this pilot study, in conjunction with previous adherence in experimental studies [ 32 , 35 , 62 ], bring increased expectations for a good adherence to the training program in further studies.…”
Section: Discussionmentioning
confidence: 99%
“…The drop-out rate reported in this study (64%) is not unique to this Couch-to-5K programme. Stevinson et al [46] reported adherence as 53 ± 27% from another Couch-to-5K programme. parkrun events have reported drop-out rates of 37% at 6 months and 46.5% at 12 months following registration [47].…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale changes in the built environment–such as improving public illumination and sidewalks’ quality–depend on public resources, public policies, and policymakers. However, since physical activity practice has an important relationship with health outcomes ( Kapoor et al, 2022 ; Stevinson et al, 2022 ), this becomes a fundamental investment at individual and population levels.…”
Section: Discussionmentioning
confidence: 99%